1986
DOI: 10.1063/1.450339
|View full text |Cite
|
Sign up to set email alerts
|

Studies of atomic oxygen in O2+CF4 rf discharges by two-photon laser-induced fluorescence and optical emission spectroscopy

Abstract: We have used two-photon laser-induced fluorescence to obtain quantitative measurements of the concentration of ground state O atoms in O2+CF4 rf discharges. Absolute calibration was achieved by generating a known concentration of atomic oxygen by UV laser photolysis of O2. Trace amounts of Ar were added to serve as an inert reference gas for concurrent optical emission measurements, in which the plasma-induced optical emission intensities from O* and Ar* lines were recorded. Emission line shapes were measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
114
0
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(127 citation statements)
references
References 25 publications
12
114
0
1
Order By: Relevance
“…Work done by previous authors has shown that application of the actinometry method does not always yield results that reflect the true atomic oxygen number density in the plasma. The validity of actinometry for atomic oxygen has been investigated for various plasma sources: RF capacitive plasma [14,15,16], ECR source [17], DC glow discharge [18], microwave source [19,20], helicon source [21], inductive source [22], and micro-scale atmospheric pressure jet source [23]. Walkrup et al [14] investigated the validity of actinometry for atomic oxygen in RF capacitive plasmas containing both pure O 2 and O 2 /CF 2 mixtures by examining line emission intensity ratios.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work done by previous authors has shown that application of the actinometry method does not always yield results that reflect the true atomic oxygen number density in the plasma. The validity of actinometry for atomic oxygen has been investigated for various plasma sources: RF capacitive plasma [14,15,16], ECR source [17], DC glow discharge [18], microwave source [19,20], helicon source [21], inductive source [22], and micro-scale atmospheric pressure jet source [23]. Walkrup et al [14] investigated the validity of actinometry for atomic oxygen in RF capacitive plasmas containing both pure O 2 and O 2 /CF 2 mixtures by examining line emission intensity ratios.…”
Section: Introductionmentioning
confidence: 99%
“…The validity of actinometry for atomic oxygen has been investigated for various plasma sources: RF capacitive plasma [14,15,16], ECR source [17], DC glow discharge [18], microwave source [19,20], helicon source [21], inductive source [22], and micro-scale atmospheric pressure jet source [23]. Walkrup et al [14] investigated the validity of actinometry for atomic oxygen in RF capacitive plasmas containing both pure O 2 and O 2 /CF 2 mixtures by examining line emission intensity ratios. The plasma emission for atomic oxygen at 844 nm O * (844), 777 nm O * (777) and argon at 750 nm Ar * (750) were recorded and the O * (844)/Ar * (750) and O * (777)/Ar * (750) ratios were monitored and compared with [O] results obtained using TALIF at a fixed total pressure of 400 mTorr.…”
Section: Introductionmentioning
confidence: 99%
“…This approach can provide a qualitative measurement of the atomic oxygen ground state density in low pressure plasmas with not too low degree of dissociation. 9 The determination of absolute O-atom densities in cold atmospheric pressure plasmas is, however, significantly more complex.…”
mentioning
confidence: 99%
“…Nevertheless, dissociative excitation can become even dominant toward lower dissociation degrees. 9 The corresponding formal extension of the actinometry approach is possible. However, detailed information on the time and space dependent EEDF in the relevant energy range is required for quantitative density determination.…”
mentioning
confidence: 99%
“…The emission from an excited state of the actinometer gas into the ground state is measured. For O 2 plasmas this actinometer gas is usually Ar [28]. The emission intensities of Ar* and O* are measured simultaneously.…”
Section: Optical Emission Spectroscopymentioning
confidence: 99%